How do you solve 3( 3m - 2) = 2( 2m + 3)?

1 Answer
Jan 26, 2018

m=12/5

Explanation:

Use distributive property. multiply the number in front of the parenthesis with each number inside the parenthesis.

3*3m= 9m

3 * (-2)=6

2*2m=4m

2*3=6

The equation now is

9m-6=4m+6

The next step is to add 6 on the left side and on the right side. This will get rid of the -6 on the left side. Your new equation is

9m=4m+12

Then you are going to subtract 4m from both sides. This will give you

5m=12

Divide both sides by 5

m = 12/5